Planktonic carbon metabolism of an underwater coral atoll in the oligotrophic sea: a case study of Zhongsha Atoll, Central South China Sea - Xiang, Chenhui; Zhong, Yu; Li, Gang; Song, Xingyu; Huang, Yadong; Wang, Zhen; Zheng, Chuanyang; Huang, Liangmin (Frontiers in Marine Science, 2023)
Coral atolls are widely recognized as oases of remarkable biodiversity and productivity within the oligotrophic open ocean. However, considerable debate surrounds the net carbon metabolism of planktonic communities in oceanic coral atolls and their contribution to the overall carbon budget of the ocean. Zhongsha Atoll, situated in the central South China Sea, represents one of the largest submerged reef atolls globally. Despite its significance, the ecological environment and characteristics of community production and metabolism at Zhongsha Atoll have been scarcely studied, and it remains uncertain whether these features differ from those observed in barrier-type reefs. In this study, we examined the gross primary production (GPP), community respiration (CR), and net community production (NCP) of the planktonic community in Zhongsha Atoll and its surrounding waters from 22 June to 6 July 2020. We also analyzed the potential influences of their distribution patterns. Our findings revealed that CR did not vary significantly with depth and it was considerably higher than GPP. As a result, the waters at the euphotic depth of Zhongsha Atoll were found to be heterotrophic, with negative NCP. Additionally, the correlation analysis demonstrated a negative relationship between NCP and CR. The NCP values were -35.28 ± 26.73 and -53.18 ± 31.77 mg C m-3 d-1 for the surface and chlorophyll maximum (DCM) layers, respectively. The NCP for the upper water column was -3023 mg C m-2 d-1. The waters above the reef flat (FL) exhibited higher primary productivity, with GPP in the surface and DCM layer being 1.61 and 2.71 times greater, respectively, than in the surrounding oceanic regions. However, the FL displayed a greater level of heterotrophy due to its stronger CR. In conclusion, the carbon metabolism of the planktonic community in submerged Zhongsha Atoll acts as a source of atmospheric CO2, and the distribution of coral reefs considerably contributes to the efficiency of carbon cycling within the atoll.